Outcomes in patients with hypertension and type 2 diabetes receiving a stent for angina - R. N. Akhtereyev; A. S. Galyavich; L. V. Baleeva; Z. M. Galeeva (Российский кардиологический журнал)
Aim. To study the outcomes in hypertensive (HTN) patients receiving a stent for class III angina, depending on concomitant type 2 diabetes (T2D).Material and methods. The study included 295 patients aged 45 to 75 years. All patients underwent coronary angiography followed by elective stenting. Clinical outcomes were evaluated after outpatient follow-up (average 44 months). Patients were divided into two groups: group 1 — 214 patients with coronary artery disease (CAD) in combination with HTN; group 2 — 81 patients with CAD in combination with HTN and T2D.Results.In the group of patients without T2D, during the follow-up period, class III angina was observed in 92 patients (43%). The decrease in systolic blood pressure (BP) (SBP) and diastolic BP (DBP) in this subgroup was 18 and 14 mm Hg, respectively (p<0,001); 35 patients (38%) had myocardial infarction (MI). In the group of patients with T2D, class III angina was recorded in 60 patients (74,1%). The decrease in SBP and DBP in this subgroup was 19 and 12 mm Hg, respectively  (p<0,001). There were 58 cases of MI in this subgroup (96,7%).Conclusion.After stent insertion, patients with CAD, HTN and T2D still reporting class III angina were more likely to have MI than patients without T2D. This indicates a greater contribution of T2D to MI development, despite an equal decrease of SBP in patients with/without T2D.